A bibliometric analysis of employee-centred corporate social responsibility research in the 2000s. Issue 5 (16th July 2019) - Low, Mei Peng; Siegel, Donald
Abstract : Purpose: This paper aims to study the knowledge development and research dissemination on employee-centred CSR research through a social network approach by adopting bibliometric analysis. Design/methodology/approach: By using the bibliometric data obtained from Scopus, descriptive analysis using social network analysis together with visualisation tool to examine the knowledge development and research dissemination on employee-centred CSR. The publications were identified by limiting search in Scopus database through keywords, namely, Corporate Social Responsibility, Employee and/or Internal Corporate Social Responsibility, from 2000 to 2018 in all document types and access type. The data were analysed by year, source of publication, author, country, affiliation, subject area and term analysis. Findings: The findings reveal that the Journal of Business Ethics and Social Responsibility Journal are the two key journals publishing in employee-centred CSR. The USA and the UK are the two main countries that dominate the publication production. Most of the publications are in the area of business, management and accounting. Main publications are contributed by Andriukaitiene, R., Swaen, V. and Vveinhardt, J. The number of publication increases marginally from year to year. More focus linkages were established between employee-centred CSR with organisational commitment and firm performance in the late 2016. Research limitations/implications: The analysis and findings are only limited to data retrieved from the Scopus database from year 2000 to 2018 on 31 December 2018. Besides, the selection of the quality criteria is based on researchers' definition of suitable empirical basis. Practical implications: The findings of this paper provide insights to the researchers on the development of CSR research has expanded to internal stakeholders. It also contributes by identifying the sources of research and its development trends in employee-centred CSR research. Social implications: The findings provide a holistic picture of domino effects of CSR initiatives in organisational behaviour. It also further reinforces the awareness internal CSR being another important perspective of CSR. Originality/value: The originality of this paper lies in its contribution in the bibliometric approach to study the dissemination trend of employee-centred CSR research from the Scopus database.